2009
DOI: 10.1248/bpb.32.578
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of Hydroxytyrosol on Oxidative Stress and Nuclear Factor-κB Activation in THP-1 Cells

Abstract: Recent publications have shown that an oxidized cytosolic environment amplifies activation of nuclear factor kappaB (NF-kB), which plays a critical role during inflammatory processes by activating many genes encoding for proinflammatory cytokines and immunoregulatory mediators.1) Some publications have also suggested that reactive oxygen species (ROS) influence inflammatory processes through mechanisms that are dependent on NF-kB.2) In the course of many inflammatory diseases reduced levels of glutathione (GSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
37
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 46 publications
(35 reference statements)
8
37
1
Order By: Relevance
“…In the present study, the administration of DOPET restrained NF-κB protein expression following SAH. This is consistent with a study conducted by Zhang et al (38), which suggested that treatment with DOPET significantly suppressed NF-κB expression in THP-1 cells. These results support the implication of the Akt/NF-κB pathway in the neuroprotective effect of DOPET in the EBI after SAH.…”
supporting
confidence: 93%
“…In the present study, the administration of DOPET restrained NF-κB protein expression following SAH. This is consistent with a study conducted by Zhang et al (38), which suggested that treatment with DOPET significantly suppressed NF-κB expression in THP-1 cells. These results support the implication of the Akt/NF-κB pathway in the neuroprotective effect of DOPET in the EBI after SAH.…”
supporting
confidence: 93%
“…In this study, we found that OO, HT, and TY co-treated animals showed resistance to the production of NO on TCDD treatment, implying that these compounds could prevent or be helpful in reducing the complications of TCDD-induced oxidative stress. Substantial evidence in the literature shows that the olive oil phenolic compound HT treatment suppresses the activation of NF-kB and attenuate oxidative stress in THP-1 cells by decreasing NO production (Zhang et al, 2009). …”
Section: Effect Of Oo Ht and Ty On Tcdd-induced Tissue Nitrite Levelmentioning
confidence: 99%
“…[10][11][12][13][14]16,17) In order to determine how the over-expression of Bcl-2 and Bcl-xL affects the NF-kappa B activity in NCI-H292 cells treated either d-elemene or b-elemene, the cells transfected with either Bcl-2 or Bcl-xL were incubated with 200 mM of d-elemene or b-elemene or vehicles. The nuclear protein was isolated after incubation.…”
Section: Over-expression Of Bcl-2 and Bcl-xl Protected Cell Death Indmentioning
confidence: 99%
“…[12][13][14][15][16] Inducible loss of NF-kappa B activity is associated with the down-regulation of anti-apoptotic Bcl-2 family members and the occurence of apoptosis. Furthermore, the promoter regions of both Bcl-2 and Bcl-xL genes contain binding sites for NF-kappa B.…”
mentioning
confidence: 99%